Through A Scientific Approach by Using Problem Solving to Improve The Ability of Mathematical Understanding of Vocanational Students - Rahman Dani; Ayi Solehudin (IKIP Siliwangi, 2018)
This research is a research through a scientific approach by using problem solving to improve the understanding of mathematical abilities of vocational students. This research is a quasi-experimental form the which aims to test the achievement and improvement of students' understanding of mathematical skills through a scientific approach, using problem solving rather than learning that only uses a scientific approach. And examine the implementation of learning steps through a scientific approach, using problem solving. The population in this study were all students of class X Vocational School in Bandung Regency, while the sample was class X students from one of the Vocational Schools roomates were determined purposively and were randomly selected from the existing class X. Based on the results of the data analysis, it was concluded that the achievement and improvement of the understanding of mathematical abilities of Vocational students who learning Obtained through the scientific approach, using problem solving was better than Reviews those who Obtained using the scientific approach learning only. And the implementation of learning through a scientific approach, using problem solving is Carried out in accordance with the planned learning steps